2004
DOI: 10.1515/jpem.2004.17.10.1393
|View full text |Cite
|
Sign up to set email alerts
|

Serum Leptin Levels in Premature Pubarche and Prepubertal Girls With and Without Obesity

Abstract: ABSTRAGTLeptin can be regarded as a marker of the nutritional status of the body. This study was performed to determine the correlation of leptin levels with insulin (I) and androgens in girls with premature pubarche (PP) and prepubertal controls (C) with (OB) or without (nOB) obesity. We studied 25 girls with PP and 14 C; girls were dived into two subgroups according to body mass index (BMI): OB (18 PP and 8 C) and nOB (7 PP and 6 C). Obesity was defined as BMI >95 th percentile for chronological age. Serum l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
4
15
0
2
Order By: Relevance
“…20,37,38 Insulin and, less remarkably, cortisol were found to have significant positive effects on serum leptin, whereas dehydroepiandrostenedione had a weaker negative influence in a multiple regression analysis using BMI as an index of degree of body fat. 39 These findings are in agreement with experimental data that demonstrate that both insulin and cortisol are stimulators of leptin expression in cultured human adipocytes. 40,41 The findings of the present study are consistent with studies demonstrating that insulin secretion is decreased in response to exercise, particularly in children, thereby increasing the peripheral consumption of glucose.…”
Section: Discussionsupporting
confidence: 89%
“…20,37,38 Insulin and, less remarkably, cortisol were found to have significant positive effects on serum leptin, whereas dehydroepiandrostenedione had a weaker negative influence in a multiple regression analysis using BMI as an index of degree of body fat. 39 These findings are in agreement with experimental data that demonstrate that both insulin and cortisol are stimulators of leptin expression in cultured human adipocytes. 40,41 The findings of the present study are consistent with studies demonstrating that insulin secretion is decreased in response to exercise, particularly in children, thereby increasing the peripheral consumption of glucose.…”
Section: Discussionsupporting
confidence: 89%
“…L'Allemand et al 19 reported that the BMI of PA patients was higher than that of the control group and leptin values were similar to those in the control group. Recently, it was reported that serum leptin levels of obese PA patients are higher than in a non-obese PA group independent of insulin and androgen levels 34 . Recently, it was reported that serum leptin levels of obese PA patients are higher than in a non-obese PA group independent of insulin and androgen levels 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic mechanisms involved in PCOS may yield new insights into the pathophysiology of the disorder [20]. Girls with premature pubarche (PP) could be considered a population at risk for plurimetabolic syndrome [21].…”
Section: Fstmentioning
confidence: 99%